2003
DOI: 10.2478/bf02476229
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of polyolefins by reactive processing

Abstract: From the study of the modi cation of PE and PP with maleic anhydride, maleic acid and an acid salt of maleic acid (sodium maleate) in a liquid or solid state, it was shown that the main controlling factor in the solid state modi cation of polyole ns is the joint plastic deformation of the system components. The changes of molecular characteristics were investigated by gel permeation chromatography. It was shown, that the molecular weight of modi ed PP samples increases at times by linking with intermolecular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Additionally, its hydrophilic character does not allow its homogeneous dispersion in the PP matrix that is hydrophobic; however, the addition of compatibilizer improved the homogeneity of the films, as shown in Figure 3(2A–2C). This behavior is consistent with the literature where it was reported that the use of polymers grafted with maleic anhydride are good compatibilizers for immiscible binary mixtures [13,14,15,16]. Moreover, films with smaller chitosan particle size (Figure 3(3A–3C)) showed better dispersion of the particles of chitosan in the PP matrix, so in these films the formation of agglomerates is almost unnoticeable, which is attributed to the good dispersion of the chitosan particles in the PP matrix.…”
Section: Resultssupporting
confidence: 93%
“…Additionally, its hydrophilic character does not allow its homogeneous dispersion in the PP matrix that is hydrophobic; however, the addition of compatibilizer improved the homogeneity of the films, as shown in Figure 3(2A–2C). This behavior is consistent with the literature where it was reported that the use of polymers grafted with maleic anhydride are good compatibilizers for immiscible binary mixtures [13,14,15,16]. Moreover, films with smaller chitosan particle size (Figure 3(3A–3C)) showed better dispersion of the particles of chitosan in the PP matrix, so in these films the formation of agglomerates is almost unnoticeable, which is attributed to the good dispersion of the chitosan particles in the PP matrix.…”
Section: Resultssupporting
confidence: 93%
“…Peroxide-initiated free radical polymerization is probably the simplest, oldest and most widely used method for the synthesis of graft copolymers which is also adaptable to a variety of commercial applications [10]. The blends of polyolefins and polyacrylates are of clear technological interest [11].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting blend of these two types of polymers is generally immiscible. Polymers grafted with maleic anhydride are used as compatibilizers for immiscible binary mixtures, showing good results …”
Section: Introductionmentioning
confidence: 99%